PENGARUH SERVICE MARKETING DAN EXPERIENTAL MARKETING TERHADAP CUSTOMER LOYALITY MELALUI CUSTOMER SATISFACTION PADA PELANGGAN MERK TOYOTA DI SURABAYA BARAT - jurnalpps pps; Rio Budi Dwitama; Indra Prasetyo; Nugroho Mardi Wibowo (Jurnal Manajerial Bisnis, 2020)
This study aims to determine the effect of Service Marketing and Marketing Experiences on consumer loyalty through Toyota customer satisfaction in West Surabaya. This research is an explanatory study with a quantitative approach. The results of observations on 96 respondents were analyzed using path analys, and it can be concluded that Service Marketing and Experiential Marketing directly influence the Customer Loyalty of Toyota customers in West Surabaya. The other results show that Service Marketing and Experiential Marketing through Customer Satisfaction have a significant effect on the customer loyalty of Toyota customers in West Surabaya.Keywords: service marketing, experiental marketing, customer loyality, customer satisfaction